Therapeutic effect and metabolomics mechanism of Patrinia Villosa (Thunb.) juss on liver injury in rats - Qiao, Li-Man; Zhang, Hui; Liu, Wei; Lou, Dan (Frontiers in Pharmacology, 2022)
Patrinia villosa (Thunb.) Juss (P.V) is widely used in the treatment of chronic diseases, such as appendicitis, enteritis and gynecological inflammation. Modern research indicated that the herb has pharmacological effect on liver injury caused by inflammation, but the metabolomics mechanism is not clear. For the purpose of discovering the therapeutic effect and metabolomic mechanism of P.V on liver injury, 40 Sprague-Dawley (SD) rats were divided into normal group, model group, and P.V groups (0.98, 1.97, and 2.96 g/kg). The model group and P.V groups were injected intraperitoneally with 40% CCl4 (v/v, olive oil) to establish liver injury model. After administration of P.V for 7 consecutive days. Therapeutic effect of P.V on liver injury rats were analyzed. P.V could decrease serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels of liver injury rats as a dose-dependent manner. Compared with the model group, the pathological analysis of liver tissue of P.V groups exhibit significant decrease tendency of hepatic tissue structure destruction, cytoplasmic vacuolation, cellular swelling, and inflammatory cell infiltration as a dose-dependent manner. 82 endogenous metabolites in rat serum and liver were analyzed by Ultra-high performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS). 14 metabolites in serum and 26 metabolites in liver were significantly different between the P.V group (2.96 g/kg) and the model group. Metabolic pathway analysis revealed that the main pathway including alanine, aspartate and glutamate metabolism, and TCA cycle were significantly altered. It is suggested that P.V can alleviate CCl4 induced liver injury, and its effect on metabolites may be an important mechanism of action.